2013
DOI: 10.1371/journal.pone.0074588
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-Seq Reveals Infection-Related Gene Expression Changes in Phytophthora capsici

Abstract: Phytophthora capsici is a soilborne plant pathogen capable of infecting a wide range of plants, including many solanaceous crops. However, genetic resistance and fungicides often fail to manage P. capsici due to limited knowledge on the molecular biology and basis of P. capsici pathogenicity. To begin to rectify this situation, Illumina RNA-Seq was used to perform massively parallel sequencing of three cDNA samples derived from P. capsici mycelia (MY), zoospores (ZO) and germinating cysts with germ tubes (GC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 74 publications
(107 reference statements)
1
47
0
Order By: Relevance
“…Members of the Crinkler (CRN) group of effectors were first identified amongst P. infestans genes that caused crinkling and necrosis when transiently expressed in N. benthamiana cells (Torto et al ., ), although more recent studies have shown that the majority of CRN effectors suppress plant defence (Chen et al ., ; Haas et al ., ; Stam et al ., ). CRN proteins have a conserved N‐terminal domain that includes LFLAK and DWL motifs that function in directing translocation of the CRN proteins from the apoplast into the plant cytoplasm (Schornack et al ., ).…”
Section: Plant–pathogen Interactionsmentioning
confidence: 98%
“…Members of the Crinkler (CRN) group of effectors were first identified amongst P. infestans genes that caused crinkling and necrosis when transiently expressed in N. benthamiana cells (Torto et al ., ), although more recent studies have shown that the majority of CRN effectors suppress plant defence (Chen et al ., ; Haas et al ., ; Stam et al ., ). CRN proteins have a conserved N‐terminal domain that includes LFLAK and DWL motifs that function in directing translocation of the CRN proteins from the apoplast into the plant cytoplasm (Schornack et al ., ).…”
Section: Plant–pathogen Interactionsmentioning
confidence: 98%
“…Natural resistance to P. capsici in pepper and cucurbits appears to be rare (Mallard et al, 2013) but, in tomato, it may be extensive (Quesada-Ocampo and Hausbeck, 2010). Recent molecular studies of the CRN class of effectors have indicated that they are often localized to the host nucleus and play an important role in the infection process (Chen et al, 2013;Stam et al, 2013aStam et al, , 2013b. Transcriptome studies using RNAseq and microarrays have indicated dramatic changes from pre-infective spores through the early biotrophic and later necrotrophic stages of infection (Chen et al, 2013;Jupe et al, 2013).…”
Section: Phytophthora Capsicimentioning
confidence: 99%
“…Recent molecular studies of the CRN class of effectors have indicated that they are often localized to the host nucleus and play an important role in the infection process (Chen et al, 2013;Stam et al, 2013aStam et al, , 2013b. Transcriptome studies using RNAseq and microarrays have indicated dramatic changes from pre-infective spores through the early biotrophic and later necrotrophic stages of infection (Chen et al, 2013;Jupe et al, 2013). Studies of individual effectors have suggested that some manipulate the host to allow infection, whereas others trigger plant cell death (Chen et al, 2013;Feng and Li, 2013;Feng et al, 2010;Sun et al, 2009).…”
Section: Phytophthora Capsicimentioning
confidence: 99%
See 1 more Smart Citation
“…Plant receptor-like kinase, such as Nicotiana benthamiana BAK1/SERK3, contributes to elicitin-mediated necrosis, and kinase gene silencing leads to enhanced plant susceptibility to P. infestans (Chaparro-Garcia et al, 2011). Furthermore, elicitin-, NLP-and CBEL-induced cell death can be suppressed by host-translocated effectors, demonstrating that oomycetes have evolved delicate mechanisms to counteract the host cell death triggered by necrosis-inducing elicitors (Bos et al, 2006;Chen et al, 2013Chen et al, , 2014Gilroy et al, 2011;Liu et al, 2011). Based on these results, it has been suggested that responses to these proteins could overlap with ETI and play an important role in the outcome of Phytophthora-plant interactions (Thomma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%